2008
DOI: 10.1128/jcm.02309-07
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Highly Virulent Strains of Streptococcus suis Serotype 2 According to Glutamate Dehydrogenase Electrophoretic and Sequence Type

Abstract: The glutamate dehydrogenase (GDH) enzymes of 19 Streptococcus suis serotype 2 strains, consisting of 18 swine isolates and 1 human clinical isolate from a geographically varied collection, were analyzed by activity staining on a nondenaturing gel. All seven (100%) of the highly virulent strains tested produced an electrophoretic type (ET) distinct from those of moderately virulent and nonvirulent strains. By PCR and nucleotide sequence determination, the gdh genes of the 19 strains and of 2 highly virulent str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Highly virulent strains of S. suis serotype 2 can be distinguished from moderately virulent and nonvirulent strains on the basis of their GDH [26,27] . The isolates of S. suis serotype 2 were divided into 3 groups according to deduced GDH amino acid sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly virulent strains of S. suis serotype 2 can be distinguished from moderately virulent and nonvirulent strains on the basis of their GDH [26,27] . The isolates of S. suis serotype 2 were divided into 3 groups according to deduced GDH amino acid sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Group I consisted of highly virulent isolates, containing Ala299-to-Ser, Glu305-to-Lys, and Glu330-to-Lys amino acid substitutions compared with groups II and III. Groups II and III consisted of moderately virulent and nonvirulent strains, which are separated from each other by Tyr72-to-Asp and Thr296to-Ala substitutions [27] . In this study, the GDH gene of 36 strains of S. suis serotype 2 obtained a 1.500-bp fragment containing an open reading frame of 1.344 nucleotides by PCR and nucleotide sequence determination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of approaches to differentiate pathogenic isolates from low virulent or avirulent ones such as virulotyping and MLST. Several putative virulence factors such as GDH, MRP, EF, CPS, SLY, and 89K have been used as virulence-associated markers for virulotyping of SS2 isolates (Baums and Valentin-Weigand 2009;Lun et al 2007;Kutz and Okwumabua 2008). MLST has been used for the typing of more than 400 SS2 isolates, and those belonging to ST1 and ST27 complexes are considered Zhejiang, lung lesion as more pathogenic (King et al 2002;Takamatsu et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The glutamate dehydrogenase (GDH) of Streptococcus suis is conserved and antigenic, as it reacts with serum from animals with S. suis type 2 infection, leading to it being utilized as a serological assay for diagnosis of S. suis infection [1,2]. It has been reported that the subunit vaccination based on GDH protein of S. suis is an effective strategy for protecting pigs against S. suis infection [3] but its market is limited because of the high cost.…”
Section: Introductionmentioning
confidence: 99%